Assessment Of The Anti-Fungal Activity Of Trichoderma harzianum Against Seed-Borne Chickpea Ascochyta Blight Under Field Conditions - Qasim A Marzani; Kamalaldeen M. Fatah (Zanco Journal of Pure and Applied Sciences, 2025)
Ascochyta rabiei (Pass.) Labr., the fungal pathogen that causes ascochyta blight, is a serious global danger to chickpea crops, especially in the Mediterranean and other colder, wetter climates. This foliar disease can cause losses of up to 50% and is particularly damaging in humid and rainy environments. Severe outbreaks frequently result in total crop destruction. Chemical control, despite providing quick and efficient intervention, presents challenges such as environmental contamination and the evolution of fungicide resistance due to the heterothallic nature of the fungus. This study aimed to explore the use of antagonistic fungi as a safer alternative for managing Ascochyta blight damage. In a field trial, the commercial product Biocont-T, containing Trichoderma harzianum, was applied as a pre-planting treatment and mixed with peat moss at various rates. The experiment followed a randomized complete block design (RCBD) and was replicated three times. Results indicated that the most effective treatment inhibiting the disease (55.55%) involved a peat-based soil inoculation mixture containing 20.8 kg/ha of Biocont-T and 2083 kg/ha of peat moss (T3). This was followed by T1 (20.8 kg/ha of Biocont-T), which inhibited the disease by 52.77%, T2 (41.66 kg/ha of Biocont-T) with a 41.66% inhibition rate, and T6 (1041.66 kg/ha of pre-inoculated peat moss with the bioagent for one week), also with a 41.66% inhibition rate. In conclusion, while using T. harzianum as a biocontrol agent did not completely eradicate the disease, it proved an effective method with no adverse environmental effects.